Perancangan Aplikasi Sistem Pakar Diagnosa Kerusakan Lift Dengan Menggunakan Metode Case Based Reasoning (CBR) - Nugraha Hadi Syaputra (JURIKOM (Jurnal Riset Komputer), 2019)
The elevator requires maintenance to make it work optimally, if the elevator does not work optimally then there will be damage that can result in users who are in the elevator could be trapped due to a jammed door and not open. Elevator damage like this needs to be put on the expert system in order to shorten the analysis time by using the Case Based Reasoning method. Case Based Reasoning is a method of solving problems by utilizing previous experience. Case Based Reasoning is one method of solving problems in finding solutions for a new case to an old case solution that has the same problem. To diagnose damage to the elevator using the Case Based Reasoning method. Users will be given questions to get the similarity value with the Case Based Reasoning formula, so that the diagnostic results and the percentage of similarity values and their probability are obtained.